Business ties, political ties, and innovation performance in Chinese industrial firms: The role of entrepreneurial orientation and environmental dynamism - Zhang, Jing A.; O'Kane, Conor; Chen, Guoquan (Journal of business research, 2020)
This research examines the integrated effects of external network ties and entrepreneurial orientation (EO) on innovation performance. It also investigates how environmental dynamism affects the network ties-EO-innovation performance relationship. Drawing on the dynamic capability perspective of EO and the contingency view of network ties, we posit that business ties influence innovation performance through EO, while political ties affect innovation performance through business ties and EO. Moreover, we hypothesize that the indirect effects of business ties (through EO) and political ties (through business ties and EO) on innovation performance are stronger in more dynamic environments. Using a sample of 218 industrial firms from China, the findings support our arguments. Our in-depth examination of the relationship between network ties, EO and innovation performance results in some theoretical and managerial implications for discussion.